Virtual Assistance Improves Diet Compliance of Hypertension Patients - Dhina Widayati; Pria Wahyu Romadhon Girianto; Markus Mete (STIKes Patria Husada Blitar, 2022)
Changes in lifestyle that are far from healthy living behavior are currently in line with the increase in hypertension which requires compliance efforts in drug consumption and diabetes management. Lack of knowledge is one of the factors of non-compliance in the management of hypertension. Mentoring is one way to increase knowledge. Knowing the effect of virtual mentoring on hypertension diet on dietary compliance of hypertension sufferers is the goal in this study. The design of the study was pre-experimental. A sample of 28 respondents was obtained by purposive sampling technique. The results of the study before being given virtual assistance showed most of the respondents (53.6%) had adequate hypertension diet compliance, while after virtual assistance showed almost all respondents (89.3%) complied in the implementation of the hypertension diet. The results of the Wilcoxon test analysis showed p: 0.000 and: 0.05, indicating that virtual assistance had an effect on dietary compliance with hypertension sufferers. Virtual assistance makes communication between patients and health workers more intense, both in the process of transferring information and controlling. Virtual mentoring interventions can be used as a method of heath education for health workers to improve dietary compliance with hypertension sufferers.